KAPŁAN W SŁUŻBIE PARTYKULARNEGO I POWSZECHNEGO KOŚCIOŁA - Dziuba, Andrzej Franciszek (Prawo Kanoniczne, 2004)
The priest is a minister or „servant of Christ” (1 Cor 4: 1), Christ who is prolonged in time and space through the signs of the Church. „The priestly ministry... (is) the ministry of the Church it self” (PO 15). The priest participates in the being, work and life of Christ the Priest, who „come... to serve” (M k 10: 45) and who „loved the Church and gave himself up for her” (Eph 5: 25). The priest’s specific spirituality comes from pastoral charity and is expressed in service to the particular or „local” church (diocese) and to the universal Church. For priests the sense of the Church and love of the Church means availability to serve her unselfishly, without „using” her and „without any thought of personal or family advantage” (AG 16). „In this way they will learn, in a wonderful manner, to give themselves fully to the service of Christ’s Body, and to the work of the Gospel; they will learn to adhere to their bishop as loyal fellow workers, and to collaborate with their brothers” (AG 16). The Church is a community of people who believe in Christ, assembled (ecclesia) by his word and saving presence. Thus it was not born from a technical process or from a simple hum an experience. „The Church cannot be separated from Christ decause he himself was its founder. By an express act of his will he founded the Church on the Twelve, with Peter as their head, establishing it as the universal and necessary sacrament of salvation” (Puebla 222). The priest’s ecclesial service as a minister is nesessarily expressed in a community or church (particular, local, diocese), presided over by a bishop, a successor of the Apostles. The Church is built up in this community, made concrete in space and time. It is the Church as an event. „W hat we have said here of the universal Church must be said also of the particular communities of Christians... of which the one Catholic Church is composed; for these also are governed by Jesus Christ through the voice and authority of their respective bishops... each of them is also, so far as his own diocese is concerned, a true Pastor who tends and rules in the name of Christ the flock committed to his care” (Mystici Corporis Christi 40). The nature of the ministerial priesthood is strictly missionary. „The spiritual gift which priests have received in ordination does not prepare them merely for a limited and circumscribed mission, but for the fullest, in fact the universal, mission of salvation «to the ends of the earth» (Acts 1: 8). The reason is that every priestly ministry shares in the fullness of the mission entrusted by Christ to the Apostles. For the priesthood of Christ, of which priests have been really made sharers, is necessarily directed to all peoples and all times, and is not confined by any bounds of blood, race, or age, as was already typified in a mysterious way by the figure of Melchizedek. Priests, therefore, should recall that the solicitude of all the churches ought to be their inimate concern” (PO 10). The priest’s accord with Christ is expressed instinctively in love of the Church: „Christ loved the Church and gave himself up for her” (Eph 5: 25). This love, in imitation of Christ, is also expressed in suffering „for the sake of his body, that is, the Church” (Col 1: 24). „Faithfulness to Christ cannot be separated from faithfulness to his Church” (PO 14).